ALKBH10B Is an RNA N 6-Methyladenosine Demethylase Affecting Arabidopsis Floral Transition. Issue 12 (27th November 2017) - Duan, Hong-Chao; Wei, Lian-Huan; Zhang, Chi; Wang, Ye; Chen, Lin; Lu, Zhike; Chen, Peng R.; He, Chuan; Jia, Guifang
Abstract : Arabidopsis ALKBH10B is a major m 6 A mRNA demethylase affecting floral transition and vegetative growth. Abstract: N 6 -methyladenosine (m 6 A) is the most abundant, internal, posttranscriptional modification in mRNA among all higher eukaryotes. In mammals, this modification is reversible and plays broad roles in the regulation of mRNA metabolism and processing. Despite its importance, previous studies on the role and mechanism of m 6 A methylation in Arabidopsis thaliana have been limited. Here, we report that ALKBH10B is a demethylase that oxidatively reverses m 6 A methylation in mRNA in vitro and in vivo. Depletion of ALKBH10B in the alkbh10b mutant delays flowering and represses vegetative growth. Complementation with wild-type ALKBH10B, but not a catalytically inactive mutant ( ALKBH10B H366A/E368A ), rescues these effects in alkbh10b-1 mutant plants, suggesting the observed phenotypes are controlled by the catalytic action of ALKBH10B . We show that ALKBH10B -mediated mRNA demethylation affects the stability of target transcripts, thereby influencing floral transition. We identified 1190 m 6 A hypermethylated transcripts in the alkbh10b-1 mutant involved in plant development. The discovery and characterization of the archetypical RNA demethylase in Arabidopsis sheds light on the occurrence and functional role(s) of reversible mRNA methylation in plants and defines the role of m 6 A RNA modification in Arabidopsis floral transition.